Narratives of Place, Belonging and Language: An Intercultural Perspective - Nic Craith, Máiréad (Palgrave Macmillan, 2020)
Examining identity in relation to globalization and migration, this book uses narratives and memoirs from contemporary authors who have lived 'in-between' two or more languages. It explores the human desire to find one's 'own place' in new cultural contexts, and looks at the role of language in shaping a sense of belonging in society...